Students Performance after Completing Lower Secondary Education: Evidence from Romania - Octavian CEBAN; Ionela-Roxana GLAVAN; Andreea MIRICA; Marian NECULA; Roxana-Violeta PARTAS-CIOLAN; Liliana CATRINA (Communications of International Proceedings, 2021)
SARS COV-19 pandemic brought back on the public agenda the inequalities in the public education system regarding access to public education facilities and impact on the performance of students when factoring for academic performance, area of residency and sex. In this paper we provide some evidence regarding mean differences between different sub-populations of students during the 2020 Romanian National Evaluation exams. The statistical procedures used for testing are t-test between population means and Pearson correlation. We also provide a few recommendations for policy makers in order to reduce the widening gaps between student sub-populations.
Keywords: Education system; academic performance; t-tests; Pearson correlation.